Hair Follicle Dermal Cells Support Expansion of Murine and Human Embryonic and Induced Pluripotent Stem Cells and Promote Haematopoiesis in Mouse Cultures - Jun Liu; Claire A. Higgins; Jenna C. Whitehouse; Susan J. Harris; Heather Crawford; Angela M. Christiano; Majlinda Lako; Nicholas Hole; Colin A. B. Jahoda (Stem Cells International)
In the hair follicle, the dermal papilla (DP) and dermal sheath (DS) support and maintain proliferation and differentiation of the epithelial stem cells that produce the hair fibre. In view of their regulatory properties, in this study, we investigated the interaction between hair follicle dermal cells (DP and DS) and embryonic stem cells (ESCs); induced pluripotent stem cells (iPSCs); and haematopoietic stem cells. We found that coculture of follicular dermal cells with ESCs or iPSCs supported their prolonged maintenance in an apparently undifferentiated state as established by differentiation assays, immunocytochemistry, and RT-PCR for markers of undifferentiated ESCs. We further showed that cytokines that are involved in ESC support are also expressed by cultured follicle dermal cells, providing a possible explanation for maintenance of ES cell stemness in cocultures. The same cytokines were expressed within follicles in situ in a pattern more consistent with a role in follicle growth activities than stem cell maintenance. Finally, we show that cultured mouse follicle dermal cells provide good stromal support for haematopoiesis in an established coculture model. Human follicular dermal cells represent an accessible and readily propagated source of feeder cells for pluripotent and haematopoietic cells and have potential for use in clinical applications.